Tantangan Guru PAI Dalam Membentuk Karakter Religius Siswa di Era Kurikulum Merdeka - Prisca, Prisca Octaria Diniyanti; Abdulloh (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2025)
This study aims to analyze the challenges faced by Islamic Religious Education (PAI) teachers in implementing the Merdeka Curriculum to shape students' religious character. Using a literature review method, this research identifies several key obstacles, including the flexibility of the Merdeka Curriculum, the influence of social environments, and students' limited understanding of religious teachings. These factors contribute to difficulties in fostering religious character effectively. The findings emphasize the need for comprehensive efforts to enhance the competence of PAI teachers through continuous professional development and curriculum adaptation. Additionally, strong collaboration between schools, families, and communities is essential to creating a supportive learning environment. By addressing these challenges, educators can better integrate religious values into the curriculum, ensuring that students develop a strong religious character while adapting to the evolving educational landscape. This study contributes to the ongoing discourse on religious education in Indonesia and provides insights for policymakers and educators in improving PAI implementation.